A Design of Parameter Optimal Iterative Learning Control for Linear Discrete-Time Systems. (28th January 2014) - Kase, Wataru
Abstract : The iterative learning control algorithm proposed by Owens and Feng, which guarantees the monotonic convergence of the tracking error norms along with the trial, will be modified. The learning gain of the proposed method will be determined through a quadratic cost function. MIMO plant case will be also discussed. Numerical simulations will be presented to confirm the validity of the proposed design.